A survey of utilizing by-products from tra catfish processing industry in vietnam - Nguyen, Van Nguyen; Le, Duc Trung; Nguyen, Thi Huong Thao; Dinh , Thi Men (Journal of Technical Education Science, 2016)
This article aims to provide some information from a survey carried out by the Research Center for Aquafeed Nutrition and Fishery Post-Harvest Technology (APOTEC) on the current status of post-harvest practices for by-product utilization from Tra catfish (Pangasius hypophthalmus) processing industry in Vietnam. A large number of seafood factories in the Mekong Delta were investigated to collect necessary information and evaluate the efficiency of using the Tra catfish by-products on both economical and environmental aspects. Apart from information collected from interviews, chemical analysis on composition of the Tra catfish by-products was also conducted for more understanding about this potential resource of seafood industry. Our investigation has identified three main problems relating to economical, technical and environmental aspects that the processors have to cope with when utilizing by-products from Tra catfish processing. For the purpose of increasing the efficiency of by-products utilization and minimizing the environmental impacts, some recommendations have been proposed including change in perception, improvement in the way of pre-treatment and collection, more investment in R&D activities and collaboration between research organizations and processors in solutions of the problems.